Worldly Love from the Perspective of the Al-Qur’an : A Thematic Analysis of the Terms Ḥubb Al-Dunyā, Al-‘Ājilah, Zīnah, and La‘ib Wa Lahwu - Zahratul Farhah (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to examine the concept of worldly love in the Al-Qur’an through an analysis of the terms ḥubb al-dunyā, al-‘ājilah, zīnah, and la‘ib wa lahwu, in order to formulate relevant ethical guidelines for Muslims in the modern era. The novelty of this study lies in its specific focus on certain terms that reflect love of the world, unlike previous studies that tended to discuss the world in general without specifying the concept of love of the world but rather focused more on the world itself. The method used is a literature review combining thematic (mauḍū’ī) and linguistic-analytical (bayānī) approaches. The results of the study classify these terms into explicit (manṭūq) and implicit (mafhūm) categories. From a bayānī perspective, the term ḥubb al-dunyā explicitly refers to the world as the object of excessive love, whereas al-‘ājilah functions as an attribute (waṣf) that emphasizes the world’s transient and fleeting nature. Implicitly, zīnah refers to objects of adornment and material luxury, while la‘ib wa lahwu describe the distracting nature of worldly life. In the contemporary context, the interpretation of love for the world in modern life has highly relevant implications for confronting the tide of materialism and maintaining a balance between material and spiritual achievements; the haste in pursuing worldly pleasures conflicts with preparation for the hereafter, while an optimistic attitude toward making the most of the world is essential Penelitian ini bertujuan untuk mengkaji konsep cinta dunia dalam Al-Al-Qur’an melalui analisis terhadap lafaz ḥubb al-dunyā, al-‘ājilah, zīnah, dan la‘ib wa lahwu, guna merumuskan panduan etis yang relevan bagi umat Islam di era modern.Kebaruan penelitian ini terletak pada spesifikasi kajian terhadap lafaz-lafaz tertentu yang mencerminkan cinta dunia, berbeda dari penelitian terdahulu yang cenderung membahas dunia secara umum tanpa mengspesifikkan konsep cinta dunia. Tetapi lebih banyak membahas tentang dunia. Metode yang digunakan adalah penelitian kepustakaan dengan kombinasi pendekatan tematik (mauḍū’ī) dan linguistik-analitis (bayānī). Hasil penelitian mengklasifikasikan lafaz-lafaz tersebut ke dalam kategori eksplisit (manṭūq) dan implisit (mafhūm). Secara bayānī, lafaz ḥubb al-dunyā secara eksplisit menunjuk dunia sebagai objek kecintaan yang berlebihan, sedangkan al-‘ājilah berfungsi sebagai sifat (waṣf) yang menekankan karakter dunia yang fana dan cepat berlalu. Secara implisit, zīnah merujuk pada objek perhiasan dan kemewahan materi, sementara la‘ib wa lahwu menggambarkan sifat kehidupan duniawi yang melalaikan. Dalam konteks kekinian, Penafsiran cinta dunia dalam kehidupan modern memberikan implikasi yang sangat relevan untuk menghadapi arus materialisme dan menjaga keseimbangan antara pencapaian material dan spiritual, ketergesaan dalam mengejar kenikmatan duniawi bertentangan dengan persiapan akhirat dan bersikap optimisme dalam memanfaatkan dunia.